ANALISIS PERAN GURU PPKn SEBAGAI EVALUATOR TERHADAP HASIL BELAJAR SISWA DI SMA SWASTA AFORE SUSUA - Cindi Mardiyanti Halawa (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2026)
The problem with this research is that teachers have not yet carried out their role as evaluators or evaluations. This research aims to (1) What is the role of PPKn teachers as evaluators at Afore Susua Private High School T.A 2023/2024. (2) What are the student learning outcomes at Afore Susua Private High School T.A 2023/2024. This type of research is qualitative research with a descriptive approach. This research was carried out from May 4, 2024 to May 31, 2024. The data source used in this research is primary data. The data collection techniques used in this research were interviews, observation and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. Based on the results of the research and discussion that have been obtained, it can be concluded that the teacher's role as an evaluator of student learning outcomes is (1) Carrying out PPKn Planning and Learning, (2) Achieving goals and carrying out evaluations of student learning outcomes, (3) Designing Instrumental Tools in Learning and (4) Reporting learning results. Evaluation can be carried out through test techniques and non-test techniques. The technical implementation of written tests can take the form of objective tests and subjective tests. To foster students' motivation to learn at Afore Susua Private High School, teachers should maximize the tools, facilities and media available in the infrastructure they already have so that they can foster motivation in students to be more enthusiastic about learning.